A Pilot-Plant Test of a Membrane Bioreactor with a Novel Membrane Made from Chlorinated Poly (Vinyl Chloride) (CPVC) and Hydroxy-Propyl Cellulose - Morita, Junsuke; Shimada, Norifumi; Higashi, Masao; Kitagawa, Tooru (Journal of Membrane and Separation Technology, 2015)
A pilot-plant test that can treat an amount of 30 ton per day of wastewater is performed. The purpose of this test is to prove the usefulness and applicability of newly developed microfiltration membranes made from chlorinated poly (vinyl chloride) and polyester nonwoven. Here, the hydrophilicity of membranes is important and hydroxyl-propyl cellulose is used to mitigate their hydrophobicity. The membrane consists of the novel structure in which small particles made from hydroxyl-propyl cellulose gel are homogeneously dispersed and attached on the surface of micro fibrils in the structure. The result of the pilot-plant test shows that the newly developed membrane has anti-fouling properties better than that of a conventional membrane made from chlorinated poly (vinyl chloride) by another company. It still shows high hydrophilicity after the use of one year, while the conventional one loses such properties. Saving electricity in producing water is one of important issues in developing membrane bioreactor systems and the case in use of newly-developed membranes is revealed to need 2.0 kWh of electricity to produce 1 m3 of filtered water. This amount is fairly good and reasonable when the pilot-plant test is considered to belong to a medium-size facility.